EVALUASI PROGRAM SANITASI TOTAL BERBASIS MASYARAKAT DI KABUPATEN MAMUJU - Agus Erwin Ashari; Fajar Akbar (Jurnal Kesehatan Manarang, 2016)
Low coverage of family latrines, village implement community-based total sanitation (STBM) and the village of defecation Random Stop (Stop Babs) resulted in increased cases of disease based environment. The purpose of this study was to determine the components of the input, process and output for the low coverage STBM program. This study is an evaluation using a qualitative approach in 10 selected health centers in Mamuju conducted by purposive sampling based health centers category in June – August 2015. The informants are holders STBM program health centers, community health centers and the head of environmental health section chief. In collecting the data, researchers used the method triagulasi ie depth interviews, observation and document analysis. Analyses were performed with a qualitative analysis of the various opinions that combined the results of triangulation. The results showed there were several indicators of input components of adequate policies, authority and responsibility, human resources; except for operational funds and infrastructure. Kompenen planning process, pengoorganisasian and reporting is adequate, but the implementation and monitoring indicators was inadequate. Output components are all yet to reach the standards set. Conclusion there are some indicators that are not sufficient operating funds, infrastructure, implementation, and monitoring.